Inappropriate use of antibiotics in the treatment of acute respiratory infections for the underfive children among general practitioners. - Iwan Dwiprahasto, Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Acute respiratory infection (ARI) is the commonest illness in children and the leading cause of morbidity and mortality in many developing countries. It comprises approximately 50% of all illness in children under five years. Unfortunately, most children are commonly treated inappropriately. A population based study involving all general practitioners (GPs) and pharmacies in Yogyakarta Special Province was carried out in June-July 1992 to provide data on antibiotic utilization for acute respiratory infection (ARI). One hundred and ninety one out of 207 GPs and all pharmacies participated in the study by completing structured form distributed during the study. Ninety three percent of patients with ARI seen by GPs were given antibiotic. Based on WHO criteria on ARI, only 7-14% of all patients were eligible to be given antibiotics. The most frequently used antibiotics for the underfives were ampicillin (38.8%) followed by cotrimoxazole (29.2%), amoxycillin (14.9%), and erythromycin (6.13%). Sixty three per cent of drug cost prescribed for the underfives children were accounted for by antibiotics. It can be concluded that inappropriate use of antibiotics was found in more than 75% patients under 5 years of age. In addition to poor indication for antibiotic use inappropriateness was also found in terms of dose, the length of antibiotic use, drug administration, and drug dosage form.Key words: ARI - innapropriate use of antibiotics - underfive children - general practitioners - prescribing pattern